A hedonic regression analysis of Houston metropolitan tax appraised land market values - Hobert, Randy (My University, 2020)
The objective of this thesis is to provide insight that policy makers can use to assess the impact of land values on prospective flood control projects in the Houston metropolitan area. Various land characteristics are regressed against county tax appraisal data on parcels of agricultural land sold within the Houston metropolitan statistical area over a 5-year period. Hedonic regressions of data from three counties found there is not a willingness to pay more for land located within any specific zip codes in the study area. However, some school district boundaries, especially those with higher median household incomes, correlate positively with higher property valuations. Land parcel size, commercial land use codes, residential improvements, paved road access, and certain suburban school districts were found to be statistically related to tax appraisals of market values. Forecasts made using tax appraisal data overestimate the actual comparable sales price of land sold in 2018. It appears that there is a relationship between better road access to transportation networks and the subdivision of farms for development, so County Commissioners and the Texas Department of Transportation should carefully weigh the risks of increasing population densities as a result of new roads constructed within and around the water pooling areas of U.S. Army Corps of Engineer levees, bypass channels, dry basin reservoirs, detention ponds, and diversion tunnels. Additionally, the strategic use of agricultural conservation easements offers a less costly alternative to fee simple property acquisitions for managing development along Cypress Creek and other tributaries of the Buffalo Bayou waterway.
Keywords: Hedonic Regression; Houston; Land Values; Agricultural Economics